Pengaruh Atribut Nasional terhadap Kebijakan Cina Bersengketa dengan Jepang di Kepulauan Diaoyu/Senkaku - Karang, Christoforus; Abil , Adam; Sharon, Maria; Pratama , Ananda; Gracia, Rafaela (Jurnal Sentris, 2023)
The dispute between China and Japan over administrative control of Diaoyu/Senkaku Islands raises a question about the intention of China with its confrontative foreign policy. China's foreign policy is often difficult to understand clearly largely because of its ambiguity in determining the appropriate instruments to fight for its interests. China's foreign policy in regards to its dispute with Japan over Diaoyu/Senkaku Islands should not have been implemented because of China's membership and ratification of UNCLOS back in 1996. By using the qualitative method along with the National Attribute theory by Valerie Hudson, it was found that China's confrontative foreign policy was based of the fact that China has an advantage on the aspects of its national attribute, mainly on its natural resources, economic and military capabilities. Keywords: Diaoyu; Senkaku; Cina; Jepang; Atribut Nasional